2016
DOI: 10.1016/j.ajpath.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Expression Profiling in Normal B-Cell Subsets and Hodgkin Lymphoma Reveals Hodgkin and Reed-Sternberg Cell–Specific Long Noncoding RNAs

Abstract: Hodgkin lymphoma (HL) is a malignancy of germinal center (GC) B-cell origin. To explore the role of long noncoding RNAs (lncRNAs) in HL, we studied lncRNA expression patterns in normal B-cell subsets, HL cell lines, and tissues. Naive and memory B cells showed a highly similar lncRNA expression pattern, distinct from GC-B cells. Significant differential expression between HL and normal GC-B cells was observed for 475 lncRNA loci. For two validated lncRNAs, an enhanced expression was observed in HL, diffuse lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…The authors detected 9955 lncRNAs in HL cell lines (DEV, L540, SUP-HD1, L1236, KM-H2, and L428) [66]. The unsupervised hierarchical cluster analysis using the 401 lncRNA differentially expressed in GC vs. naïve and memory B cells, showed that HL cell lines had a differential expression pattern close to GC B cells.…”
Section: Lncrnas In Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors detected 9955 lncRNAs in HL cell lines (DEV, L540, SUP-HD1, L1236, KM-H2, and L428) [66]. The unsupervised hierarchical cluster analysis using the 401 lncRNA differentially expressed in GC vs. naïve and memory B cells, showed that HL cell lines had a differential expression pattern close to GC B cells.…”
Section: Lncrnas In Hlmentioning
confidence: 99%
“…Moreover, RNA-FISH of the three lncRNAs in four cHL cases revealed a tumor cell-specific staining. The authors suggested that LINC00461 and FLJ42351 could act as cis-regulatory elements for MEFC2 and SLC20A1, respectively [66]. …”
Section: Lncrnas In Hlmentioning
confidence: 99%
“…7C and Table 1). Analysis of our previously published microarray data in GC-B cells and cHL cell lines [29], showed a significantly decreased gene expression level in cHL cell lines compared to GC-B cells for 4 genes i.e. BTG2 (B-cell translocation gene 2), PELI1 (E3 Ubiquitin-Protein Ligase Pellino Homolog 1), TIAM1 (T-Cell Lymphoma Invasion And Metastasis 1) and SMAD7, whereas 1 gene, i.e.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…2,3 For example, tumor-specific expression and aberrant expression of lncRNAs compared with normal tissue has been identified in prostate cancer (PCA3 and PCGEM1), 4,5 lung cancer (MALAT1), 6 breast cancer (HOTAIR), 7 and colon cancer (PINT). 8 In this issue of The American Journal of Pathology, a novel study by Tayari et al 9 compared the expression profiles of lncRNAs in normal B-cell subsets [naïve, germinal center (GC), memory B-cells] and Hodgkin lymphoma (HL) cells. The study identified distinct expression patterns of lncRNAs among the normal B-cells and between normal B-cells and HL cells.…”
mentioning
confidence: 99%
“…Indeed, molecular pathways that regulate normal B-cell development are also involved in pathogenesis of lymphomas, and several malignant lymphomas originate from distinct stages of normal Bcell development. 17 The study by Tayari et al 9 gave insight toward the identification of a specific lncRNA expression pattern for normal B-cells as well as for HL B-cells. It was shown that there is a dynamic regulation of lncRNA and mRNA expression during the normal B-cell maturation with an expression change of 251 lncRNA loci during the transition from naïve to GC-B cells and a reversion toward levels comparable to naïve B-cells during the differentiation to memory B-cells.…”
mentioning
confidence: 99%